Enhancing EFL Listening Comprehension through a Customized Immersive Virtual Reality Application: A Study on Computer Science Students - Shally Amna; Dian Christina; Randy Permana; Wienda Gusta (FKIP Universitas Lampung, 2026)
Enhancing EFL Listening Comprehension through a Customized Immersive Virtual Reality Application: A Study on Computer Science Students. Listening comprehension is a crucial component of language acquisition, yet it remains a persistent challenge for students across diverse fields of study. Objective: This study develops a Virtual Reality app to address a gap and enhance computer science students' listening comprehension skills. Methods: This study employed a quantitative design with a paired t-test and a Likert-scale questionnaire. The participants in this study are 20 students from the Computer Science Faculty at the University of Putra Indonesia, YPTK Padang. Pre-test and Post-test were administered to evaluate improvements in listening Comprehension, as shown by a t-value of -5.501 and a p-value of < .001, while a questionnaire was also given to assess students' experiences and opinions after using the VR app. Findings: The VR app design required a few improvements in device settings, yet it still significantly enhances students' English comprehension skills, as shown by a paired t-test, and practically increases students' motivation. Conclusion: A VR app can be used in language learning to improve students' abilities, increase their motivation, and reduce anxiety, especially in listening comprehension. Keywords: EFL students, listening comprehension, virtual reality.